Pembatasan Diversi Terhadap Anak Ancam Pidana Penjara Lebih 7 Tahun dalam Sistem Peradilan Pidana Anak - Erik Wahyu Setiawan; Frans Simangunsong (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Diversion, which emphasizes resolving issues through restorative justice as opposed to the standard criminal court procedure, is a crucial component of the juvenile criminal justice system. However, Law Number 11 of 2012's Article 7 paragraph (2) on the juvenile criminal justice system only permits the use of diversion for acts that are not repeat offenders and carry a sentence of less than seven years in prison. This clause raises legal questions concerning how effectively these limitations align with the concepts of fair treatment for all, child safety, and the best interests of the child. This study aims to investigate the reasons behind the various regulations pertaining to youngsters who may be imprisoned for more than seven years. Additionally, this study examines whether these restrictions adhere to Indonesia's juvenile justice system's child protection regulations. This study uses two different methods: one related to laws and another based on ideas. Legal documents were gathered by researching laws and rules in libraries, along with books and other legal sources. They were then studied in a descriptive and analytical way using qualitative methods. Research shows that diversion restrictions are meant to keep a fair balance between protecting children, taking care of victims' needs, and serving the good of society in how the law is enforced. However, rules that only look at how serious the criminal danger is don't take into account the child's personal situation or how likely they are to turn their life around. Because of this, some people worry that it might make it harder for children to get to places where they can recover. Therefore, more adaptable methods of rerouting cases according to each child's circumstances better align with the fundamental principles of child protection and the objectives of the juvenile criminal justice system, which are centered on providing for children, aiding in their recovery, and promoting their social reintegration.